The echoes of Jane Eyre - Kocsis-S. Anikó Katalin; Csetényi Korinna (1999)
In my thesis I am writing about three novels: Jane Eyre by Charlotte Bronte, Wide Sargasso Sea by Jean Rhys and Rebecca by Daphne du Maurier. There are three chapters in my thesis. The first part is about the three writers and the three novels, in the second one I am writing about the female characters in the novels and in the third one about the male characters. I ended my work with a selection of pictures to illustrate the text. My aim was to show the similarities in these three novels from different aspects. The conclusion is that there are a lot of similarities in them. Jane Eyre and Rebecca have common features in their style and theme, Jane Eyre and Wide Sargasso Sea are similar in the characters. There are many elements taken from real life experiences in all of the novels. Nature and different symbols play a significant part in them and other important questions concern the role of women in marriage and the role of sexuality. I found that the most important, deciding factors in all the three novels were the descriptions of the heroines' inner life, the development of their souls and their lives shown through a psychological aspect.
Keywords: Pedagógusképzés